CURRENT APPROACHES TOX-RAY METHODS OF DIAGNOSTICS IN PLANNING OF DENTAL IMPLANTS AND STAGES OF SURGICAL REHABILITATION OF PATIENTS WITH A SECONDARY EDENTIA - H.B. Prots; V.P. Puryk; Y.I. Solodzhuk; G.P. Nychyporuk; I.G. Omelchuk; Y.V. Puryk; A.K. Shudjairi; S.A. Ohiyenko; I.I. Prots (Ukrainian Medical Stomatological Academy, 2016)
Abstract. Inflammatory and degenerative processes in periodontal tissues in 80% of cases involve loss of teeth. The basic method of orthopedic treatment of patients with chronic forms of generalized periodontitis (GP), which is usually accompanied by loss of teeth, is prosthetic dental bridges [3,4,8]. At 42.8 - 87.4% of the prevailing reason that enhances inflammatory degenerative processes is abnormal overload of the tooth supporting tissues. This greatly aggravates during chronic GP: it promotes the formation of periodontal pockets, baring the necks of the teeth and inflammation in the area of marginal periodontium [1,2,8]. The general rule for periodontal treatment is to eliminate etiologic factors for the normalization of its properties. The best orthopedic treatment is defined to be a structure with additional support on endosseous implants [5,6]. As a result of redistribution of the load on teeth and implants, the occlusal periodontal trauma is reduced, or even eliminated, atrophy of the edentulous jaw areas under the influence of functional overload slows by 2-3 times [5,10]. Many periodontists recommended gradual and consistent implementation of all periodontal procedures, which significantly increases the length of treatment and is burdensome for working patients [2,3,9]. Possibilities and conditions of performing one surgery visit on periodontal tissues and implantation in patients with varying severity of chronic GP generally are not enough researched. The aim of our study is to improve the treatment of patients with partial edentia and chronic generalized periodontitis by including dental implantation to the complex of therapeutic measures. Materials and methods. We examined 225 patients with secondary edentia, aged 30-65, who had planned dental implantation. A cone-beam computer tomography was conducted to 167 patients by the cone-beam tomography Morita (JMorita MFG Corp.). Results. The planning of the dental implantation by the cone-beam computer tomography determinates implantation opportunity of toothless jaw segment and is based on the evaluation of the indicators of implantation area: height and width of alveolar process, type of the bone tissue and mineral density. At the values of the height of alveolar process on the lower jaw - 10-14±0,2 mm, and on the upper jaw 9-12±0,3 mm, at the width alveolar process 3-5 mm, type of the bone tissue D1-D3 (Misch), and at the value of mineral density from 950- 1600. It was determined the positive implantation ability of toothless jaw segment in 64,2% patients. Conclusions • Dental implantation in patients with mild GP can achieve consistently good results regardless of treatment. Simultaneous surgery on periodontal tissues and dental implantation 1.5-2 times reduces treatment without reducing its quality. • In patients with moderate and severe GP, it is appropriate to conduct stepwise surgical interventions, following dental implantation to prevent postoperative complications and implant loss. • When planning for dental implants and periodontal surgical intervention it is necessary to identify markers of bone remodeling to assess the structural and functional state of bone tissue and prescribe osteotrophic drugs that promote positive postoperative period